2020
DOI: 10.1155/2020/1705964
|View full text |Cite
|
Sign up to set email alerts
|

Laser Acupuncture Alleviates Symptoms and Improves Quality of Life in Women with Overactive Bladder: A Double‐Blind, Pilot Randomized Controlled Trial

Abstract: Objective. The aim of this study was to investigate the clinical efficacy of laser acupuncture for the treatment of women with overactive bladder (OAB) in Taiwan. Methods. A double-blind randomized controlled trial was conducted on female patients with OAB symptoms referred from gynecologists, and subjects were divided into two groups using blocked randomization. LaserPan (RJ-Laser, Germany) was applied to seven selected acupuncture points. The subjects received laser acupuncture 3 times per week for 3 weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…This review revealed 6 studies that used conventional acupuncture, 15 , 17–20 1 used laser acupuncture. 16 The retention time for each treatment is 20~30 min and most tend to 20 min. The session varies from 1 to 8 times, except in the trial of Chang et al 16 The vast majority of treatment sessions are over 4 weeks long.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This review revealed 6 studies that used conventional acupuncture, 15 , 17–20 1 used laser acupuncture. 16 The retention time for each treatment is 20~30 min and most tend to 20 min. The session varies from 1 to 8 times, except in the trial of Chang et al 16 The vast majority of treatment sessions are over 4 weeks long.…”
Section: Resultsmentioning
confidence: 99%
“…Acupuncture treatment appeared to be safe and well-tolerated and feasible. Chang 2020 16 15 56.4±14.3 years 10 wet OAB and 5 dry OAB Subjects in the verum laser acupuncture group received a total energy of 6 joule at each acupoint with frequency prescribed, 611Hz~1102Hz, 9 sessions for 3 weeks KI3 (Taixi), SP6 (Sanyinjiao), CV4 (Guanyuan), CV6 (Qihai), BL33 (Zhongliao), BL34 (Xialiao), GV20 (Baihui) OABBS 8.7±1.8 vs 4.7±2.4 in week 1 and 3.4±1.9 in week 2 and 3.1±1.6 in week 3 ( p <0.01); UDI-6 6.0±2.5 vs 3.5±1.9 in week 1 and 2.3±1.8 in week 2 and 2.4±1.6 in week 3 ( p <0.05); IIQ-7 9.9 ± 5.7 vs 4.2±2.3 in week 1 and 4.2±3.2 in week 2 and 3.0±2.5 in week 3 ( p <0.05) Laser acupuncture can alleviate OAB symptoms and improve quality of life and could be an effective therapy for women with OAB. Aydoğmuş 2014 17 28 38±12.9 years all OAB dry Acupuncture, 20 min, 8 session for 4 weeks LI4 (Hegu), GV22 (Xinhui), SP6 (Sanyinjiao), ST36 (Zusanli), LR3 (Taichong), GV29 (Yintang), CV4 (Guanyuan), KI3 (Taixi), KI5 (Shuiquan) NFG,0.92pg/mL (range 0.70–2.45) vs 0.07 (range 0.01–2.82); symptom scores 21 (range 14–21) vs 5 (range 2–20); quality of life scores 2.0 (1–3) vs 2.0 (range 0–3), all the results had been significantly improved after treatment ( p <0.01) In patients with OAB in whom anticholinergic treatment is contraindicated, acupuncture may be considered another treatment option.…”
Section: Resultsmentioning
confidence: 99%
“…The two acupuncture treatment points applied in our study are commonly used to manage OAB in traditional Chinese/Korean medicine [ 14 ]. CV6 is called Qihai, the Sea of Qi, located 1.5 cun inferior to the umbilicus, and CV4 is called Guanyuan, Gate of Origin, located 3 cun inferior to the umbilicus [ 9 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used the device known as the Woman Stress-Free (Color DNA-WSF; Color Seven Co., Seoul, Korea), which consists of a power supply unit and two microprocessor-controlled light-emitting diodes which direct the LLLT to two acupuncture points. We selected two of the acupuncture points often used to treat OAB, namely, conception vessel (CV) 6 (Qihai) and CV4 (Guanyuan) [ 14 ]. We hypothesized that a skin-adhesive LLLT device applied at two acupuncture points might be an effective treatment for OAB.…”
Section: Introductionmentioning
confidence: 99%
“…3,14,17 The stimulation of acupuncture points using non-thermal, low-intensity laser irradiation is commonly referred to as laser acupuncture, 18 which is thought to improve nocturnal enuresis by increasing bladder capacity and reducing detrusor muscle contractility and maximum bladder contraction pressure. 19,20 Moxibustion refers to the stimulation of acupoints with burning moxa wool and has been proposed to regulate the autonomic nervous system, which is responsible for bladder control. 16,21 However, there is a lack of consensus regarding the potential mechanisms underlying the beneficial effects of various forms of acupuncture for the treatment of nocturnal enuresis in children.…”
Section: Introductionmentioning
confidence: 99%